1992
DOI: 10.1111/j.1438-8677.1992.tb00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Autumn Leaves of Ginkgo biloba L.: Optical Properties, Pigments and Optical Brighteners

Abstract: Senescent leaves of Gingko biloba accumulate fluorescent compounds which may contribute to the golden luminous appearance of the autumnal foliage. Apart from the putative effect of such optical brighteners, the changes of spectral optical properties associated with senescence are due to the breakdown of chlorophyll in conjunction with a remarkably high retention of carotenoids. Carotenoid esters accumulate concomitant with chlorophyll breakdown. Optical properties in the infrared range of the spectrum illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Despite the spectacular color, the mechanism underlying leaf coloration in G. bilob a remains poorly understood. In an early study of G. biloba , Matile et al 11 . reported that spectral optical properties change due to retention of carotenoids in yellow leaves in the autumn.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the spectacular color, the mechanism underlying leaf coloration in G. bilob a remains poorly understood. In an early study of G. biloba , Matile et al 11 . reported that spectral optical properties change due to retention of carotenoids in yellow leaves in the autumn.…”
Section: Introductionmentioning
confidence: 99%
“…Autumn colours are produced (Sanger, 1971;Matile, 2000;Lee and Gould, 2002) by two main classes of compound: carotenoids (yellow-orange) and anthocyanins (red-purple), although in some cases other pigments are used (for example 6-hydroxykynurenic acid for the brilliant yellow of Ginkgo biloba; Matile et al, 1992). Whereas carotenoids are present all year round and become visible during leaf senescence because of the degradation of chlorophyll (Biswal, 1995), anthocyanins are actively produced in autumn (Sanger, 1971;Lee and Gould, 2002).…”
Section: Autumn Coloursmentioning
confidence: 99%
“…In addition to di¡erential pigment decomposition, colour change also results from the synthesis of new compounds. A number of £uorescent compounds and optical brighteners have been recorded only in autumn leaves (Duggelin et al 1988;Matile et al 1992). The case against a simple economy is even stronger for the anthocyanin reds and purples because they are manufactured in often massive quantities in autumn leaves (Boyer et al 1988;Ji et al 1992), suggesting a major energetic cost to red autumnal colour.…”
Section: (A) Autumn Coloration Is Expensivementioning
confidence: 99%